Nonlinear mixed‐effects modeling as a method for causal inference to predict exposures under desired within‐subject dose titration schemes - Christian Bartels; Martina Scauda; Neva Coello; Thomas Dumortier; Björn Bornkamp; Giusi Moffa (CPT: Pharmacometrics & Systems Pharmacology)
Abstract The ICH E9 (R1) guidance and the related estimand framework propose to clearly define and separate the clinical question of interest formulated as estimand from the estimation method. With that it becomes important to assess the validity of the estimation method and the assumptions that must be made. When going beyond the intention to treat analyses that can rely on randomization, causal inference is usually used to discuss the validity of estimation methods for the estimand of interest. In pharmacometrics, mixed‐effects models are routinely used to analyze longitudinal clinical trial data; however, they are rarely discussed as a method for causal inference. Here, we evaluate nonlinear mixed‐effects modeling and simulation (NLME M&S) in the context of causal inference as a standardization method for longitudinal data in the presence of confounders. Standardization is a well‐known method in causal inference to correct for confounding by analyzing and combining results from subgroups of patients. We show that nonlinear mixed‐effects modeling is a particular implementation of standardization that conditions on individual parameters described by the random effects of the mixed‐effects model. As an example, we use a simulated clinical trial with within‐subject dose titration. Being interested in the outcome of the hypothetical situation that patients adhere to the planned treatment schedule, we put assumptions in a causal diagram. From the causal diagram, conditional independence assumptions are derived either by conditioning on the individual parameters or on earlier outcomes. With both conditional independencies unbiased estimates can be obtained.